Hubungan Motivasi Kerja Perawat Dengan Pelaksaan Kominikasi Efektif SBAR Saat Timbang Terima Pasien - Aprilianti, Hemi (Jurnal Health Society, 2025)
Introduction: The quality of nursing services is reflected through nurses' effective communication, which can prevent misinformation during the weigh-in process and ensure patient safety, one of which is the application of SBAR communication. The purpose of this study was to determine the relationship between nurses' work motivation and the implementation of SBAR effective communication during patient weigh-in in the inpatient room of Bhakti Medicare Hospital Cicurug. Methods: Correlational research through cross-sectional approach. All nurses in the inpatient room of Bhakti Medicare Cicurug Hospital became the population with a sample of 81 respondents using proportional random sampling. Questionnaires were used as data collection media. Bivariate analysis using Somers'd test. Results: The results showed that most respondents had high motivation and performed SBAR communication in the good category. There is a relationship between nurse work motivation and the implementation of SBAR effective communication with p-value = 0.000 (<0.05). Conclusion: There is a relationship between nurses' work motivation and the implementation of SBAR 2effective communication when weighing patients in the inpatient room of Bhakti Medicare Hospital Cicurug.